A clinicopathological study of primary cutaneous amyloidosis - Dr. Madhavi A. Kulkarni; Dr. Tejeshwini Patil; Dr. Padma Shree Solanki (Tropical Journal of Pathology and Microbiology, 2019)
Background: Primary localized cutaneous amyloidosis (PCA) is a common problem encountered in dermatology outpatient characterized by deposition of amyloid in dermis without any systemic involvement. Three subtypes have been recognized namely Macular, Papular (Lichen) and Nodular forms. Histopathological examination of the lesions reveals amorphous eosinophilic deposits in papillary dermis which stain positively with congo red. Aim: To study and correlate the clinical and histological profile of all three forms of primary cutaneous amyloidosis. Materials and Methods: A total number of 85 cases of primary cutaneous amyloidosis were included in the study. After a detailed history and complete examination, the patient was subjected to skin biopsy from the affected area. The clinical and histopathological findings obtained were analyzed and results correlated. Results: Of the 85 cases of Primary localized cutaneous amyloidosis, 43 cases (50.6%) were of Lichen amyloidosis and 36 cases (42.35%) were Macular amyloidosis. 6 cases (7%) were biphasic amyloidosis. Most of patients were in the age group of 21-50 years with slight female predominance 1:1.3. Majority of the cases of Lichen amyloidosis involved the pretibial area where as Macular amyloidosis affected the upper back and extensor aspect of arms. Histopathologically, the epidermis showed hyperkeratosis and irregular acanthosis which was more prominent finding in Lichen amyloidosis than the macular form. In both these variants there was expansion of dermal papillae by amyloid deposits showing positive congo red staining. Conclusions: Similar demographic profile and histopathological characteristics between Lichen and Macular amyloidosis suggests that these two forms are closely related variants of a single disease.